Miniaturised wideband ingestible antenna for wireless capsule endoscopy. Issue 4 (19th February 2020) - Biswas, Balaka; Karmakar, Ayan; Chandra, Vikash
Abstract : This study demonstrates the development of an electrically small wideband antenna on silicon substrate targeting wireless capsule endoscopy application. Operating frequency is chosen as 915 MHz. Proposed antenna exhibits a wide frequency bandwidth of 300 MHz (750–1050 MHz) experimentally for a very compact size of 0.021 λ0  × 0.021 λ0 mm 2 . To simulate the realistic human body environment, 'male Torso' model has been considered surrounding this miniaturised antenna. Different tissue properties have been considered during simulation by altering the electrical properties of the human phantom. For the practical experiment, 'colon' tissue has been considered and fabricated prototype antenna is tested in this liquid. Further to study the bio‐compatibility, specific absorption rate of the antenna is evaluated. Theoretically, the whole antenna assembly along with the phantom is modelled and corresponding link budget calculation is also accomplished to estimate carrier to noise ( C / N 0 ) ratio. Link margin coming out from this study indicates the suitability of the proposed antenna in biomedical applications. Orientation of the capsule in the gastrointestinal tract, effect of capsule material and the effect of capsule's in‐side electronics upon antenna performance have been studied in this work. Experimentation reveals very promising results, which closely resembles with the predicted simulated values.